Protein S-palmitoylation modification: implications in tumor and tumor immune microenvironment - Chen, Yijiao; Li, Yongsheng; Wu, Lei (Frontiers in Immunology, 2024)
Protein S-palmitoylation is a reversible post-translational lipid modification that involves the addition of a 16-carbon palmitoyl group to a protein cysteine residue via a thioester linkage. This modification plays a crucial role in the regulation protein localization, accumulation, secretion, stability, and function. Dysregulation of protein S-palmitoylation can disrupt cellular pathways and contribute to the development of various diseases, particularly cancers. Aberrant S-palmitoylation has been extensively studied and proven to be involved in tumor initiation and growth, metastasis, and apoptosis. In addition, emerging evidence suggests that protein S-palmitoylation may also have a potential role in immune modulation. Therefore, a comprehensive understanding of the regulatory mechanisms of S-palmitoylation in tumor cells and the tumor immune microenvironment is essential to improve our understanding of this process. In this review, we summarize the recent progress of S-palmitoylation in tumors and the tumor immune microenvironment, focusing on the S-palmitoylation modification of various proteins. Furthermore, we propose new ideas for immunotherapeutic strategies through S-palmitoylation intervention.